Functional composite polymer electrolytes with imidazole modified SiO2 nanoparticles for high-voltage cathode lithium ion batteries. (10th October 2019) - Wu, Jinhua; Zuo, Xiaoxi; Chen, Qiuyu; Deng, Xiao; Liang, Huiyin; Zhu, Tianming; Liu, Jiansheng; Li, Weijie; Nan, Junmin
Abstract: Poly(vinylidene ﬂuoride-co-hexaﬂuoro-propylene) doped with imidazole-modified silica nanoparticles (Z-SiO2 ) is coated in a polyethylene substrate to form a functional composite polymer electrolyte (PVDF-HFP-(Z-SiO2 )/PE-based CPEs) and used for high voltage LiNi0.5 Co0.2 Mn0.3 O2 cathode lithium-ion batteries (LIBs). The imidazole-based modified SiO2 nanoparticles are first prepared via a distillation precipitation polymerization. The composite separators with 30 wt% Z-SiO2 nanoparticles prepared via a dip-coating process exhibits a porous and uniformly dispersed morphology and enhanced performance, including excellent electrolyte uptake (310%), high ionic conductivity of 1.03 mS cm −1, and oxidative decomposition voltage up to 4.75 V. More importantly, a stable cathode electrolyte interphase (CEI) layer can be formed, endowing the Li/PVDF-HFP-(Z-SiO2 )/PE-based CPEs/LiNi0.5 Co0.2 Mn0.3 O2 (NCM523) cells superior cycling stability and rate capability (169 mAh g −1, 81.9%) under when the charge cut-off voltage increased to 4.5 V, which is higher than that assembled with PE separator (160 mAh g −1, 40.8%). These results demonstrate that the Z-SiO2 nanoparticles not only act as the fillers of the CPEs but also are water/acid scavengers in favor of the formation of a stable CEI film, which promotes the cycling performance and rate capability of high voltage NCM523 cathode and reveals promising prospect for practical applications in LIBs at high voltage operation. Graphical abstract: Image 1 Highlights: The Z-SiO2 was synthesized by a distillation-precipitation polymerization method. A functional CPEs was prepared by doped with Z-SiO2 . The Z-SiO2 as water/acid scavengers in favor of the formation of a stable CEI layer. Li/CPEs/NCM523 cell exhibits a good cycling stability under high voltage.